2018
DOI: 10.1155/2018/8272313
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Leiomyoma in the Colon Masquerading as Other Types of Colonic Pedunculated Polyps

Abstract: We describe two cases of leiomyoma in the colon that were diagnosed histologically after endoscopic resection. The first case was a 79-year-old Japanese woman who presented with a pedunculated polyp of 14 mm length at the splenic flexure. Preoperative diagnosis suggested a colonic mucosubmucosal elongated polyp. The second case was a 29-year-old Japanese woman who presented with a pedunculated polyp of 40 mm length at the hepatic flexure and had an ulcer on top of the polyp. Preoperative diagnosis suggested an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Choi et al reported that only about 46% of colorectal leiomyomas were diagnosed accurately based on their endoscopic features [ 6 ]. Ikeda et al speculated this could be due to the scarcity of leiomyomas occurring as pedunculated lesions; thus, physicians are less likely to identify them morphologically [ 11 ]. However, the rate of accurate diagnosis of colorectal leiomyoma has been increasing with the increased frequency of screening colonoscopies [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Choi et al reported that only about 46% of colorectal leiomyomas were diagnosed accurately based on their endoscopic features [ 6 ]. Ikeda et al speculated this could be due to the scarcity of leiomyomas occurring as pedunculated lesions; thus, physicians are less likely to identify them morphologically [ 11 ]. However, the rate of accurate diagnosis of colorectal leiomyoma has been increasing with the increased frequency of screening colonoscopies [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 Unlike the more common esophageal leiomyomas arising from the muscular layer and thus presenting as subepithelial tumors, colonic leiomyomas arise from the muscularis mucosae and infrequently can present as semipedunculated or pedunculated lesions. 10 An inverted diverticulum often occurs in the background of diverticular disease and histologically appears either normal or with mild chronic inflammation in mucosa and submucosa. Endoscopic resection may result in perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Large lesions can cause abdominal pain, intestinal obstruction, rectal bleeding, and perforation [2,4,7]. Surgery is the treatment of choice for large leiomyomas [9,10]. Small leiomyomas can appear as conventional polyps, which may alter the method used for removal.…”
Section: Casementioning
confidence: 99%